THE EFFECT OF CONCENTRATION AND TIME VARIATIONS OF THE LACTOSE AND SKIM MILK AS INDUCER ON THE EXPRESSION OF THE RECOMBINANT PROTEIN A224L AFRICAN SWINE FEVER VIRUS - Ardianita Triana Devi; i Gusti Ngurah Kade Mahardika; Gusti Ayu Yuniati Kencana (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
The development of subunit vaccines for African Swine Fever Virus (ASFV) requires efficient recombinant protein production. One of the potential vaccine candidate proteins is A224L, which plays a key role in inducing host cell apoptosis. This study evaluated the effectiveness of IPTG, lactose, and skim milk as inducers for the expression of recombinant A224L protein fused with GST in the pGEX-2TK-A224L plasmid. The tested concentrations of lactose and skim milk were 1%, 2.5%, and 5%, with observation times of 5, 24, and 48 hours after induction. The expression of GST-A224L was detected using dot blot with anti-GST antibody. The density of the dot was quantified using ImageJ software. The results showed that the type of inducer had a significant effect on the expression intensity of the recombinant GST-A224L protein. In addition, inducer concentration variations produced significant differences in signal intensity. Meanwhile, longer induction times did not yield stronger signal intensity. The 5% skim milk for 24 hours of induction produced the strongest signal equivalent to IPTG for 48 hours. This condition is recommended for application in the production of the ASFV A224L recombinant protein.